2016
DOI: 10.1249/mss.0000000000000754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Standing and Light-Intensity Activity on Ambulatory Blood Pressure

Abstract: Compared with sitting, accumulating 2.5 h of light-intensity physical activity or standing during an 8-h workday may reduce ABP during and after work hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(141 citation statements)
references
References 32 publications
4
133
3
1
Order By: Relevance
“…All other conditions with lower power or speed (eg, treadmill 1.6 km/hour ; cycling 5 W ) did not result in an increase in bmp. Zeigler et al 8 monitored HR during a 12-hour period (08:00–20:00) and were specifically interested in two periods (ie, work hours (08:00–16:00) and postwork hours (16:00–20:00)). Results from the 12-hour period showed an increase of 4 bpm for both treadmill 1.6 km/hour and cycling 20 W conditions compared with standing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All other conditions with lower power or speed (eg, treadmill 1.6 km/hour ; cycling 5 W ) did not result in an increase in bmp. Zeigler et al 8 monitored HR during a 12-hour period (08:00–20:00) and were specifically interested in two periods (ie, work hours (08:00–16:00) and postwork hours (16:00–20:00)). Results from the 12-hour period showed an increase of 4 bpm for both treadmill 1.6 km/hour and cycling 20 W conditions compared with standing.…”
Section: Resultsmentioning
confidence: 99%
“…Cox et al 14 found no difference in SBP and DBP measured during an intervention comparing standing and treadmill workstations. The second study8 monitored ambulatory blood pressure on adults with overweight or class 1 obesity meeting prehypertensive or impaired fasting glucose criteria over a 12-hour period (08:00–20:00). During the 12-hour period, a reduction of 2 mm Hg for cycling 20 W and 1 mm Hg for treadmill 1.6 km/hour was reported in SBP compared with standing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite evidence suggesting this level of energy expenditure is unlikely to result in meaningful body weight loss, others have shown simply breaking up prolonged sitting time with periods of standing or light physical activity can improve measures of health including endothelial cell function, ambulatory blood pressure, and altered expression of genes involved in carbohydrate metabolism [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Alkhajah et al [9] found sit-stand workstations significantly reduced office workers' sitting time during work and led to reduced sedentary time at home. Sit-stand workstations were also found to reduce upper back and neck pain, improve mood states, and reduce ambulatory blood pressure [10][11].…”
Section: Purposementioning
confidence: 99%